A new class of Ion-acoustic solitons that can exist below critical Mach number - Lakhina, G. S.; Singh, S. V.; Rubia, R. (My University, 2020)
It is commonly believed that ion-acoustic solitons can only exist above the critical Mach number in a plasma system. A new class of ion-acoustic solitons that can exist below the critical Mach number is reported for the first time in a three-component plasma consisting of hot Maxwellian electrons, and two counterstreaming ion beams. The analysis is based on the Sagdeev pseudopotential technique, and considers a simple case of two counterstreaming proton beams with equal density and streaming velocity. Linear stability analysis shows that the slow ionacoustic modes become unstable due to ion beam instability when the beam velocity normalized with the ion acoustic speed, U0, is in the range of 0.55 U0 1.14. It is shown that when the normalized streaming velocity is below or at a threshold value, Uth = 1.14, only the regular solitons having Mach numbers greater than critical Mach number can exist. However, when the streaming velocity exceeds the threshold value (all modes are stable), both regular and the new class of ion-acoustic solitons can exist. A special case of unequal ion densities and unequal streaming velocities of the counterstreaming beams is considered in appendix, and similar effects are found. Hence, the new class of slow ion-acoustic solitons can exist in the parametric regime where the system is stable to counterstreaming ion beams instability. The results could be useful in the interpretation of slow electrostatic solitary waves (ESWs) observed in the magnetosphere.
Keywords: Slow ion-acoustic solitons; Electrostatic solitary waves; Nonlinear ion-acoustic waves; Multi-ion plasma system